Analisis Penggunaan Diksi dan Gaya Bahasa pada Berita Kompas.com tentang Rendahnya Literasi dan Numerasi Siswa Indonesia - Shinta Nur Fadilah; Inez Khansa Monica; Putri Nabila Sulfa; Mohamad Afrizal (Pusat Riset dan Inovasi Nasional, 2026)
The language used in online news media plays an important role in shaping public understanding of educational issues. This study aims to analyze the use of diction and figurative language in a Kompas.com news article entitled “Mengapa Kemampuan Literasi dan Numerasi Siswa Indonesia Masih Rendah?” published on December 6, 2023. This research employed a qualitative descriptive method using document analysis techniques. The data consisted of words, phrases, and sentences containing specific diction and language styles related to literacy and numeracy issues in Indonesia. The results indicate that the news article employs evaluative diction, factual diction, causal diction, and critical diction. In addition, several language styles were identified, including comparative-argumentative style, scientific expository style, conceptual metaphor, and direct criticism. These linguistic choices function to strengthen the credibility of information, construct public awareness, and emphasize the urgency of improving literacy and numeracy achievement among Indonesian students. The findings demonstrate that journalistic language serves not only as a medium of information delivery but also as a tool for shaping readers' perceptions regarding educational problems.